SEESAW CLASS APPLICATION: ITS EFFECT ON STUDENTS’ SPEAKING SKILL - Kusmaryani, Woro; Ramli, Ramli; Hidayat, Resti (Universitas Borneo Tarakan, 2024)
In digital era, seesaw application becomes alternative platform used to connect and learn. It also contains updated contents as sources of speaking practices. The research was to investigate the significant effect of Seesaw Application on students’ speaking skills in the eleventh grade at SMK Kesehatan Kaltara. The method of study was quasi-experimental. The sample of this research was the eleventh-class nursing A as the experimental class and the eleventh-class nursing B as the control class selected through a purposive sampling technique. The research instrument was classified as pre-test and post-test and used the Independent Sample T-test to analyze the data. This research showed a significant difference between students taught using the seesaw class application and those taught using conventional methods in teaching speaking. As a result, the hypothesis test determined that the significant factor was smaller than 0.05, and the resulting t-test (2.367) was more effective than the t-table (2.045). This study implied the optimalization of application to support the students’ Speaking learning.